2013
DOI: 10.1371/journal.pone.0052876
|View full text |Cite
|
Sign up to set email alerts
|

Distortions in Development of Intestinal Microbiota Associated with Late Onset Sepsis in Preterm Infants

Abstract: Late onset sepsis (LOS) is a major contributor to neonatal morbidity and mortality, especially in premature infants. Distortions in the establishment of normal gut microbiota, commensal microbes that colonize the digestive tract, might increase the risk of LOS via disruption of the mucosal barrier with resultant translocation of luminal contents. Correlation of distortions of the intestinal microbiota with LOS is a necessary first step to design novel microbiota-based screening approaches that might lead to ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
173
7
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(203 citation statements)
references
References 26 publications
19
173
7
4
Order By: Relevance
“…The origin of LOS has traditionally been linked to colonization of intravascular catheters, however, recent studies demonstrated genetic incongruity between organisms isolated from blood culture and bacteria cultured from intravascular catheter tip, suggesting another origin [63][64][65]. Studies shown genetic similarity between cultured LOS pathogens and isolates from the gastrointestinal tract, indicating LOS pathogens might originate from the gut [66][67][68][69][70][71][72]. Therefore, Berkhout et al studied fecal VOC profiles in 36 preterm infants with confirmed LOS and compared these to 40 non-LOS controls.…”
Section: Late Onset Sepsismentioning
confidence: 99%
“…The origin of LOS has traditionally been linked to colonization of intravascular catheters, however, recent studies demonstrated genetic incongruity between organisms isolated from blood culture and bacteria cultured from intravascular catheter tip, suggesting another origin [63][64][65]. Studies shown genetic similarity between cultured LOS pathogens and isolates from the gastrointestinal tract, indicating LOS pathogens might originate from the gut [66][67][68][69][70][71][72]. Therefore, Berkhout et al studied fecal VOC profiles in 36 preterm infants with confirmed LOS and compared these to 40 non-LOS controls.…”
Section: Late Onset Sepsismentioning
confidence: 99%
“…This suggests that the absence of certain non pathogenic microorganisms -rather than the presence of pathogenic microorganisms in itself-may be one of the risk factors for the development of neonatal sepsis. 18 A study carried out in low birth weight newborn infants at a NICU showed that the risk factor for multi-drug resistant Enterobacteriaceae was prior maternal colonization. 19 …”
Section: First Month Clostridium Spp (6%-20%)mentioning
confidence: 99%
“…Esto sugiere que la ausencia de ciertos microorganismos no patógenos, más que la presencia de patógenos per se, sería uno de los factores de riesgo para el desarrollo de sepsis neonatal. 18 Un estudio en neonatos de bajo peso al nacer en una UCIN mostró que el factor de riesgo de adquisición de enterobacterias multirresistentes era la colonización previa de la madre.…”
Section: Primera Semanaunclassified
“…Los enterococos, enterobacterias, Acinetobacter sp., Pseudomonas aeruginosa pueden aislarse en la piel y convertirse en patógenos Tabla 2. Colonización del tracto intestinal en neonatos con y sin sepsis [9][10][11][12][13][15][16][17][18][19] oportunistas y ser responsables de infecciones asociadas al cuidado de la salud. 10,22 Los microorganismos más frecuentemente implicados en la etiología de la sepsis de origen intrahospitalario son los que colonizan la piel, el tracto gastrointestinal, las mucosas y los diferentes sistemas de monitorización y soporte.…”
Section: Colonización De La Pielunclassified